2017
DOI: 10.1248/yakushi.17-00153
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Prevents Dendritic Cells from Inducing Novel Inflammatory T Cells That Produce Abundant Interleukin-13

Abstract: Vitamin A (VA) plays critical roles in gut homeostasis. Dendritic cells in mesenteric lymph nodes (MLN-DCs) can metabolize VA to retinoic acid (RA), thereby inducing gut-tropic lymphocytes and enhancing peripheral diŠerentiation of regulatory T cells expressing forkhead box P3. We found that MLN-DCs from VA-deˆcient mice induced a distinct in‰ammatory T helper type 2 (Th2)-cell subset that produced abundant interleukin-13 (IL-13) and expressed receptors for homing to skin and in‰ammatory sites but not to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…ATRA can only bind to RARs, while 9-cis retinoic acid can bind to both RARs and RXRs, indicating that both ATRA and 9-cis retinoic acid can transmit signals through RARs to downstream regulatory effects [42]. The effect of RA on IL-13 may be tissue-speci c. On the one hand, RA can prevent dendritic cells in the mesenteric lymph nodes (MLN-DCs) from inducing the production of IL-13 by in ammatory Th2 cells [43,44]. However, it was also found that ATRA and 9-cis RA promote the synthesis of IL-4, IL-5, and IL-13 in PBMC cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…ATRA can only bind to RARs, while 9-cis retinoic acid can bind to both RARs and RXRs, indicating that both ATRA and 9-cis retinoic acid can transmit signals through RARs to downstream regulatory effects [42]. The effect of RA on IL-13 may be tissue-speci c. On the one hand, RA can prevent dendritic cells in the mesenteric lymph nodes (MLN-DCs) from inducing the production of IL-13 by in ammatory Th2 cells [43,44]. However, it was also found that ATRA and 9-cis RA promote the synthesis of IL-4, IL-5, and IL-13 in PBMC cells [42].…”
Section: Discussionmentioning
confidence: 99%